Maintaining pipeline integrity through holistic asset management. (2016) - El-Akruti, Khaled; Zhang, Tieling; Dwight, Richard
A review of the concept of engineering asset management (EAM) and its role in integrity management within the context of energy pipelines has been conducted. The EAM system is shown to be concerned with pipeline integrity assurance at any point of the asset life. The effectiveness of a holistic EAM approach to assuring pipeline integrity is explored through case studies for pipelines that transport high pressure natural gas or liquid petroleum. The research examines the EAM system activities, data available and information flow and decision mechanisms utilised in industry and their effectiveness in incorporating the management or control of coating degradation and external corrosion into pipeline integrity management. The objective is to provide a holistic approach to defining the status of the EAM system that is in current use in energy pipeline organisations and to examine the role of EAM in integrity management of these pipelines. [Received 30 September 2014; Revised 15 June 2015; Accepted 21 March 2016]